Cerebrospinal fluid drainage options for posthemorrhagic hydrocephalus in premature neonates - José Roberto Tude Melo; Rosane Klein Passos; Marcelo Liberato Coelho Mendes de Carvalho (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective The literature describes various cerebrospinal fluid (CSF) drainage techniques to alleviate posthemorrhagic hydrocephalus in preterm newborns; however, consensus has not been reached. The scope of this study was describing a case series of premature neonates with posthemorrhagic hydrocephalus and assessing the outcomes of different approaches used for CSF diversion. Methods A consecutive review of the medical records of neonates with posthemorrhagic hydrocephalus treated with CSF drainage was conducted. Results Forty premature neonates were included. Serial lumbar puncture, ventriculosubgaleal shunt, and ventriculoperitoneal shunt were the treatments of choice in 25%, 37.5% and 37.5% of the cases, respectively. Conclusion Cerebrospinal fluid diversion should be tailored to each case with preference given to temporary CSF drainage in neonates with lower age and lower birth-weight, while the permanent ventriculoperitoneal shunt should be considered in healthier, higher birth-weight neonates born closer to term.